1998
DOI: 10.1042/bj3310727
|View full text |Cite
|
Sign up to set email alerts
|

Human cathepsin K cleaves native type I and II collagens at the N-terminal end of the triple helix

Abstract: Cathepsin K (EC 3.4.22.38) is a recently described enzyme that has been shown to cleave type I collagen in its triple helix. The aim of this study was to determine if it also cleaves type II collagen in the triple helix and to identify the helical cleavage site(s) in types I and II collagens. Soluble human and bovine type II collagen, and rat type I collagen, were incubated with cathepsin K before the reaction was stopped with trans-epoxysuccinyl-l-leucylamido-(4-guanidino)butane (E-64). Analysis by SDS/PAGE o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
208
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 316 publications
(217 citation statements)
references
References 40 publications
5
208
1
3
Order By: Relevance
“…1), which was in a similar range to the inhibition found after the addition of the synthetic control GRGDS peptide. Triple helical type I collagen which contains in its ␣1 and ␣2 chains a total of 7 RGD motifs, is cleaved by catK at multiple sites and generates low molecular weight fragments (39,40), which may contain small soluble RGD containing peptides. The presence of soluble RGD-motif containing peptides was further supported by the loss of inhibitory effect when catK-digested collagen fragments were further degraded by trypsin before addition to cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1), which was in a similar range to the inhibition found after the addition of the synthetic control GRGDS peptide. Triple helical type I collagen which contains in its ␣1 and ␣2 chains a total of 7 RGD motifs, is cleaved by catK at multiple sites and generates low molecular weight fragments (39,40), which may contain small soluble RGD containing peptides. The presence of soluble RGD-motif containing peptides was further supported by the loss of inhibitory effect when catK-digested collagen fragments were further degraded by trypsin before addition to cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic mouse models have provided evidence supporting its important role in arthritis. Interestingly, cathepsin K is one of the few non-collagenase enzymes capable of degrading native fibrillar collagen types I and II [148]. Owing to the lack of adequate cross reactivity between the rat and human isoenzymes, animal models using cathepsin K inhibitors have been developed mostly in monkeys, and data have shown that inhibiting cathepsin K results in the prevention of bone loss.…”
Section: Drugs/agents That Target Bone Remodellingmentioning
confidence: 99%
“…Among the collagenolytic proteases, several mammalian matrix metalloproteinases (MMPs, peptidase family M10), serine proteases isolated from Uca pugilator (family S1), and cathepsins K and L from animals (family C1) have been extensively studied, and their collagen degradation mechanisms have been explored (11)(12)(13)(14)(15)(16)(17)(18)20). Some bacterial extracellular metalloproteases in the M9 family, primarily from the Vibrio (21) and Clostridium strains (22,23), also show strong collagenolytic activity.…”
mentioning
confidence: 99%